Declining Financial Capacity in Mild Cognitive Impairment: A Six-Year Longitudinal Study. (31st March 2018) - Martin, Roy C; Gerstenecker, Adam; Triebel, Kristen L; Falola, Michael; McPherson, Tarrant; Cutter, Gary; Marson, Daniel C
Abstract: Objective: To investigate financial skill decline over a 6-year period in persons with mild cognitive impairment (MCI) presumed due to Alzheimer's disease (AD). Methods: Study participants were cognitively normal (CN) older adults ( n = 82) and adults with MCI ( n = 91) based on consensus conference diagnosis. Participants completed baseline and up to six annual follow-up assessments that included standardized financial skills measurement (Financial Capacity Instrument; FCI; nine FCI domain and two global scores). We examined FCI change over time using mixed-model repeated measures analysis adjusted for baseline age and follow-up duration. Results: At baseline, the CN group performed better than the MCI group across both global and seven domain scores. Group × Time interaction effects (all p 's< .02) were found for all global and domain scores. The largest interaction effects were observed for complex domains of Financial Conceptual Knowledge, Checkbook Management, Bank Statement Management, and Bill Payment (all p 's <.0001). Annualized decline in the MCI group's global scores, calculated in relation to CN group performance, was 10–17% over the initial 3-year time span and 22–24% at 6 years. Decline in FCI domain scores ranged from 6% (Knowledge of Assets/Estate) to 22% (Investment Decision-Making) at 3 year follow-up, and from 15% (Basic Monetary Skills) to 37% (Financial Judgment) at 6 year follow-up. Conclusions: Over a 6-year period, persons with MCI demonstrated significant declines in multiple financial skills and in particular financial judgment. The findings highlight the importance of ongoing oversight by family members and clinicians of financial skills and activities in persons with MCI.